The Effect of Jack Knife Stretching and Nordic Hamstring Exercise on the Hamstring Muscle Flexibility of Futsal Athletes - Ilham Jaya Kusumah; Komarudin; Widi Kusumah; Geraldi Novian (Universitas Negeri Semarang, 2025)
The purpose of this study is to examine whether there is a significant effect of jack knife stretching and Nordic hamstring exercise on the hamstring muscle flexibility of futsal extracurricular students at state junior high school 7 Cimahi, and to determine whether there is a significant difference in the effects between jack knife stretching and Nordic hamstring exercise on the hamstring muscle flexibility of these students. The method used in this study is an experimental method with a Two Groups Pretest and Posttest Design. The population in this study consisted of 22 male students from state junior high school 7 Cimahi who participated in the futsal extracurricular program. The sample also consisted of 22 students, selected using the total sampling technique, which means the entire population was used as the sample. The sample was then divided into two groups using the ABBA formula. The treatment was conducted over 15 sessions (3 times per week). To measure hamstring muscle flexibility, the researcher used the Sit and Reach Test instrument. The Shapiro-Wilk test was used to test data normality, the Paired t-test was used to test the effect, and the Independent t-test was used to compare the effects. The results after the data analysis, a significance value of 0.000 was obtained, indicating that there is a significant effect from the treatment of jack knife stretching and nordic hamstring exercise. Data analysis showed that there was no significant difference in the effects between jack knife stretching and Nordic hamstring exercise. It can be concluded that both jack knife stretching and Nordic hamstring exercise have an effect on hamstring muscle flexibility.